Political Corruption, Income Inequality and Poverty in Nigeria: Array - Ojo, Lucas B.; Eusebius, Amadi Chibuike; Ifeanyi, Okoh Johnson; Aderemi, Timothy Ayomitunde (Acta Universitatis Danubius. Relationes Internationales, 2020)
The aim of this study is to examine the relationship between political corruption, income inequality and poverty between 2000 and 2019 in Nigeria. The study utilized secondary data from World Bank Development Indicators, Transparency International and the National Bureau of Statistics in Nigeria, and fully modified ordinary least square and Granger causality were employed to address the objective of the study. Consequently, the findings that emerged in this work could be enunciated thus; political corruption and income inequality have a significant negative relationship. However, corruption and poverty head count have an insignificant direct relationship. In the same vein, corruption and exchange rate have a significant positive relationship. In addition, there is a unidirectional causality which runs from political corruption to income inequality. Similarly, political corruption Granger causes exchange rate. Also, there is one way feedback relationship flowing from exchange rate to inflation rate. However, no feedback relationship exists between political corruption and income inequality in one hand, and political corruption and exchange rate on the other hand. In a nutshell, it could be concluded that political corruption is responsible for the rise in poverty level in Nigeria, Also, political corruption Granger causes income inequality in Nigeria. Against this backdrop, the study makes the following recommendations to the policy makers in Nigeria that any time the goal of the policy makers is to reduce poverty and inequality of income among the Nigerians, policy that will address political corruption should be of the priority. In the same line, ant graft institutions such as EFCC and ICPC should be strengthened in order to achieve their primary goals of curbing corruption in Nigeria.